2016
DOI: 10.1159/000443798
|View full text |Cite
|
Sign up to set email alerts
|

Smoking-Related Home Oxygen Burn Injuries: Continued Cause for Alarm

Abstract: Background: Home oxygen therapy is a mainstay of treatment for patients with various cardiopulmonary diseases. In spite of warnings against smoking while using home oxygen, many patients sustain burn injuries. Objectives: We aimed to quantify the morbidity and mortality of such patients admitted to our regional burn unit over a 6-year period. Methods: A retrospective chart review of all patients admitted to a regional burn center from 2008 through 2013 was completed. Admitted patients sustaining burns secondar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
7
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 9 publications
2
7
1
1
Order By: Relevance
“…In agreement with previous studies, we suggest that there is a need to update the guidelines regarding smoking during LTOT 2,12,16. Efforts to cease smoking should be optimized.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In agreement with previous studies, we suggest that there is a need to update the guidelines regarding smoking during LTOT 2,12,16. Efforts to cease smoking should be optimized.…”
Section: Discussionsupporting
confidence: 91%
“…This is in line with studies from the USA, where the mean age of patients on LTOT with burn injuries, was 62–64 years, ie, significantly younger than the LTOT patients in general 1,12,13. A previous study has shown that at least 21% of Danish COPD patients on LTOT were still smoking, and the smokers were on average 2.3 years younger than the nonsmokers 5.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Individuals with COPD on home oxygen are at increased risk of burn [1214]. Sharma et al found that the absolute risk of burn in patients prescribed oxygen therapy was 2.98 per 1000 patients compared with 1.69 per 1000 patients not prescribed oxygen during a 22-month period [15].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent issue of Respiration , Carlos et al [9] report their experience with smoking-related home oxygen burn injuries. Their aim was to quantify the morbidity and mortality of these events over a 6-year period by reviewing the charts of all patients admitted to their large regional burn center with approximately 350 admissions per year.…”
mentioning
confidence: 99%